Growth and biofilm formation by Listeria monocytogenes in cantaloupe flesh and peel extracts on four food-contact surfaces at 22 °C and 10 °C. (October 2017) - Abeysundara, Piumi De Abrew; Dhowlaghar, Nitin; Nannapaneni, Ramakrishna; Schilling, Mark W.; Chang, Sam; Mahmoud, Barakat; Sharma, Chander S.; Ma, Din-Pow
Abstract: The nationwide listeriosis outbreak that occurred in the United States during 2011 highlighted the importance of preventing cantaloupe contamination with Listeria monocytogenes ( Lm ) within farm and processing environments. The objectives of this study were to determine the effects of strain and temperature on growth and biofilm formation of Lm in cantaloupe flesh and peel extracts on different food-contact surfaces. Growth of Lm strains was markedly greater at high concentration of cantaloupe extracts and temperature in comparison to low concentration and temperature. For 50 mg/ml of cantaloupe extract inoculated with 3 log CFU/ml, the growth of Lm was 8.5 log CFU/ml in 32 h at 22 °C and 6–7 log CFU/ml in 72 h at 10 °C. For 2 mg/ml of cantaloupe extract that was inoculated with Lm, the growth was 7–7.5 log CFU/ml in 72 h at 22 °C and 3.5 log CFU/ml in 72 h at 10 °C. There were no differences ( P > 0.05) among Lm strains for biofilm formation in cantaloupe extracts, but biofilm formation was greater at high temperature and high concentration. For 50 mg/ml cantaloupe extracts inoculated with 3 log CFU/ml, the biofilm formation of Lm on stainless steel surface was approximately 7 log CFU/coupon at 22 °C in 4–7 days and 5–6 log CFU/coupon at 10 °C in 7 days. For 2 mg/ml cantaloupe extracts, the biofilm formation of Lm on the stainless-steel surface was approximately 5–6 log CFU/coupon at 22 °C and 4–4.5 log CFU/coupon at 10 °C in 7 days. The biofilm formation by cantaloupe outbreak strain Lm 2011L-2625 in cantaloupe extracts was least on buna-n rubber when compared to stainless steel, polyethylene and polyurethane surfaces ( P  < 0.05). These findings show that a very low concentration of nutrients from cantaloupe flesh or peel can induce Lm growth and subsequent biofilm formation on different food-contact processing surfaces. Highlights: Low concentration cantaloupe extracts can induce Lm growth and biofilm formation. Lm 2011L-2625 biofilms was least on buna-n rubber when compared to other surfaces. No differences in biofilm formation for six Lm strains tested in cantaloupe extracts. Lm biofilms increased with higher conc. of cantaloupe extracts at 20 °C and 10 °C.